The Sense of Belonging to the Country: Integrative Relationships and Spatiotemporal Commitment - Kolesovs, Aleksandrs (Frontiers in Psychology, 2021)
The satisfaction of the need to belong reflects in the sense of being an integrative part of the group or social system. There is some lack of empirical evidence for the structure of this sense at the macro level. This study assessed a two-dimensional model of the sense of belonging to the country, which included relational and spatiotemporal components. Participants were 539 university students from 18 to 50 (74% females). Questions regarding involvement, perceived acceptance, sense of commonality, and feeling at home represented the relational component of the sense of belonging. Four temporal categories – the recent past, present, and the near and distant future – were included in the assessment of its spatiotemporal component. A confirmatory factor analysis revealed an acceptable fit of the two-factor model. Its convergent validity was demonstrated by the association with an explicit single-item measure of belonging. The predictive effect of the spatiotemporal component emphasized the importance of continuity of belonging in considering emigration. In sum, the results confirmed the complexity of the sense of belonging to the country and the interconnectedness of integrative relationships and spatiotemporal commitment and revealed functional differences between them.